2021
DOI: 10.3389/fchem.2021.654308
|View full text |Cite
|
Sign up to set email alerts
|

Macro and Trace Elements in Hemp (Cannabis sativa L.) Cultivated in Greece: Risk Assessment of Toxic Elements

Abstract: The accumulation of hazardous contaminants in Cannabis sativa L. raises warning signs regarding possible adverse effects on human health due to the consumption of herbal medicines and/or other herbal edible products made from cannabis. Thus, there is an urge to investigate the levels of hazardous contaminants, such as heavy metals, in cannabis plant. In the present study, 29 macro and trace elements, including both beneficial and toxic elements (heavy metals and metalloids), were investigated in 90 samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…All the samples were analysed using an ICP-MS (Thermo iCAP-RQ, Thermo Fisher Scientific, San Jose, CA, USA), equipped with an ASX-280 autosampler, as described in detail in previous publications of our analytical group [ 47 ]. Briefly, for the quantification of the 27 macro and trace elements, Ni sample and skimmer cones, a Quartz cyclonic spray chamber and a MicroMist U-Series Nebulizer (0.4 mL/min with PEEK connector) were used.…”
Section: Methodsmentioning
confidence: 99%
“…All the samples were analysed using an ICP-MS (Thermo iCAP-RQ, Thermo Fisher Scientific, San Jose, CA, USA), equipped with an ASX-280 autosampler, as described in detail in previous publications of our analytical group [ 47 ]. Briefly, for the quantification of the 27 macro and trace elements, Ni sample and skimmer cones, a Quartz cyclonic spray chamber and a MicroMist U-Series Nebulizer (0.4 mL/min with PEEK connector) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The EDI of the metal element was calculated according to the method of the US Environmental Protection Agency ( USEPA, 1989 ). The HQ and CHQ of the metal elements were calculated according to the methods of Zafeiraki et al (2021) and Shen et al (2022) . …”
Section: Methodsmentioning
confidence: 99%
“…These values are comparable to values for cannabis leaves published in other studies. For example, a study by Zafeiraki et al reported Cannabis samples from various regions in Greece with analogous concentrations: 7.1 to 19.8 thousand ppm for Mg, 24.0 to 123.2 thousand ppm for Ca, 76.8 to 518 ppm for Mn, 135 to 1338 ppm for Fe, 8.2 to 64.2 ppm for Cu and 23 to 157 ppm for Zn [ 23 ]. As in the study of Greece, the predominant elements from those analyzed in Ghana cannabis samples was Ca and K, followed by Mg, Mn and Fe.…”
Section: Resultsmentioning
confidence: 99%